Reaction mechanism and microstructure development of ZrSi2 melt-infiltrated Cf/SiC-ZrC-ZrB2 composites: The influence of preform pore structures - Xiaowu Chen; Dewei Ni; Yanmei Kan; Youlin Jiang; Haijun Zhou; Zhen Wang; Shaoming Dong (Journal of Materiomics, 2018)
Reactive melt infiltration (RMI) is an effective method for fabrication of highly dense carbon fiber reinforced ultra-high temperature ceramic matrix composites (Cf/UHTCs). In this work, Cf/SiC-ZrC-ZrB2 composites were fabricated by infiltrating ZrSi2 melt into porous Cf/B4C-C preforms, where the physical and chemical reactions involved during the RMI process were identified and analyzed. Inhomogeneous infiltration between the inter- and intra-bundle pores was revealed, and was found to be strongly related to the pore structures of the Cf/B4C-C preform. It is indicated that the inhomogeneous infiltration can be mitigated remarkably with increasing porosity and pore size of the preform. The effect of pore size on the RMI process was also investigated by a quantitative model, which agrees very well with the experiment results. It further indicates that the inhomogeneous infiltration can also be relieved at elevated RMI temperature. However, excessive infiltration at elevated temperature or more porous preform may cause serious erosion on interphase and fibers, leading to mechanical properties deterioration of the final composites. Keywords: Reactive melt infiltration (RMI), Inhomogeneous infiltration, Pore structures, Mechanical properties